Impact of Trauma on Psychological Adjustment of In-School Adolescents in Benue and Nasarawa States, Nigeria - Ayim, Edunghu Martha; Agbe, Nancy (dialektika kontemporer, 2025)
This study examined the impact of trauma on the psychological adjustment of in-school adolescents in Benue and Nasarawa States, Nigeria. Guided by three research questions and three hypotheses, the study employed an ex-post facto research design. The population comprised 124,698 students from 622 public secondary schools. A sample of 399 students was selected through a multi-stage sampling procedure. Data were collected using the Trauma and Psycho-Academic Adjustment Questionnaire (TPAQ), developed by the researcher. The instrument's content and face validity were established through expert review, while a pilot test conducted on 40 students confirmed its test-retest reliability, yielding a high overall Cronbach’s Alpha coefficient of 0.93. Data were analyzed using Mean Score and Standard Deviation for the research questions, while chi-square statistics were used to test the hypotheses at a 0.05 significance level. The findings revealed that trauma significantly impacted the self-esteem, self-efficacy, anxiety, and depression levels of in-school adolescents. Based on these findings, the study concluded that trauma adversely affected the psychological adjustment of in-school adolescents in Benue and Nasarawa States. Consequently, it was recommended that school authorities and policymakers implement trauma-informed counseling services to help students manage anxiety and depression, thereby improving their emotional well-being and academic performance.